ANALYSIS OF FACTORS AFFECTING PAYLATER USAGE AMONG GENERATION Z STUDENTS: PERSPECTIVES ON SHARIA CONSUMPTION BEHAVIOR, SHARIA FINANCIAL BEHAVIOR, AND SALES PROMOTION - B. Miftahulzannah Siregar; Muhammad Ikhsan Harahap; Faisal Umardani Hasibuan (UIN Sunan Gunung Djati Bandung, 2026)
This study examines the effect of Sharia Consumption Behavior, Sharia Financial Behavior, and Sales Promotion on PayLater Usage among Generation Z students at the Faculty of Islamic Economics and Business, Universitas Islam Negeri Sumatera Utara. Previous studies have discussed PayLater mainly through financial technology adoption, consumptive behavior, and promotional influence, while limited attention has been given to the paradox in which Muslim students who understand Sharia economic principles continue to use digital credit services. Addressing this gap, this study positions PayLater Usage as a negotiated financial behavior shaped by internal Sharia-oriented controls and external digital market stimuli. A quantitative causal research design was applied, involving 98 respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics. The results show that Sharia Consumption Behavior, Sharia Financial Behavior, and Sales Promotion each have positive and significant effects on PayLater Usage. Sharia Financial Behavior emerged as the strongest predictor, followed by Sharia Consumption Behavior and Sales Promotion. Simultaneously, the three variables significantly explained PayLater Usage, with an F-value of 32.973 and an Adjusted R² of 0.497. Theoretically, this study contributes to Islamic economics literature by explaining the coexistence between Sharia-based awareness and digital consumer culture through the principle of hifzh al-mal. Practically, the findings highlight the need to strengthen Sharia financial literacy through applied digital financial ethics.